KONSEP VISUALISASI PADA DATA PENGUNJUNG KERAJAAN KASEPUHAN CIREBON: KONSEP VISUALISASI PADA DATA PENGUNJUNG KERAJAAN KASEPUHAN CIREBON - Ezra Balqis Alka Ceria; Tora Fahrudin; Ersy Ervina; Azhar Muhammad Fuad (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2025)
Keraton Kasepuhan is one of the historical relics in Cirebon, West Java, which is currently the centre of cultural preservation and development. As a cultural tourism destination, a data-driven strategy is required for visitation management and promotion of sustainable tourism development. The purpose of this study is to present a visual representation of tourist visitation data in Kasepuhan Cirebon for the period between June and August 2024. This presentation will facilitate the analysis of visitation trends based on ticket type, time of visit and payment method. The resulting visualisation will provide a more accessible representation of complex data. This research uses a data visualisation methodology. The initial dataset was sourced from Curaweda and then subjected to graphical analysis using techniques such as bar charts, pie charts and tree maps. The purpose of these visualisations was to facilitate the understanding of complex data. This research study explores the integration of data visualisation and technology frameworks in the context of tourism management in Keraton Kasepuhan Cirebon. The analysis uses data visualisation techniques to examine visitation trends, focusing on differentiating factors such as ticket type, time of day and payment method. The results showed that the pass (Kawasan, Museum Pusaka and Dalem Agung Pakungwati) contributed the most revenue (41.7%), with the highest number of visitors in the afternoon. The study also revealed that cash payment methods still dominate compared to digital payment methods. These findings highlight the important role of technology in facilitating transactions, online promotions and real-time data management. The research offers several solutions, including optimising opening hours, implementing special promotions and using data analytics technology to improve management efficiency. The research provides a comprehensive framework for cultural destination managers looking to implement data-driven strategies to increase visitor capacity and economic contribution. This research can visualise tourism visitation trends to support the strategic management of Keraton Kasepuhan. The findings can be used for more effective and sustainable cultural tourism planning and development. This research demonstrates the importance of data visualisation technology in supporting data-driven management of tourist destinations.